Dual mobilization of buried microplastics and organic carbon driven by seagrass degradation: a case study from Swan Lake, China - Huang, Yuzhou; Yu, Shuo; Zheng, Zhenming; Xiao, Xi; Zhu, Zuhao; Deng, Liangchao; Wei, Huihua; Liang, Jiani; Chen, Shuilan; Holmer, Marianne (Frontiers in Marine Science, 2025)
Seagrass beds are significant sinks for microplastics. However, the degradation of seagrass beds poses significant challenges, and evidence regarding its impacts on microplastic sinks remains scarce. In this study, sediment cores were collected to investigate microplastic stock and composition, microplastic carbon, and organic carbon stock in Zostera japonica seagrass bed and adjacent degraded area in a lagoon Swan Lake, China. The microplastic stock in seagrass bed (84.5 ± 18.5 million particles ha-1) was found significantly higher than degraded area (51.8 ± 0.6 million particles ha-1), resulting in release of 38.7% of buried microplastics reactivated in water column. Similarly, 30.0% of the microplastic carbon stock and 66.1% of the total organic carbon stock were eroded due to seagrass degradation. The carbon stocks derived from microplastics were estimated at 0.19 ± 0.10 kg C ha-1 in the seagrass bed and 0.13 ± 0.11 kg C ha-1 in the degraded area, contributing minimally to the total organic carbon stock (0.0023% and 0.0026%, respectively). Notably, seagrass degradation within a single year may trigger rapid erosion of organic carbon and microplastics buried for over 20 years in Swan Lake. A linear relationship was observed between sediment microplastic carbon and total organic carbon contents (Organic carbon = 1990 + 35100 × Microplastic carbon, R² = 0.26, p < 0.001). Microplastics in the sediments were predominantly fiber (48.1%), black (40.7%), 250–500 µm (47.0%) microplastics in degraded area, while plate (26.7%), blue and transparent, each contributing 26.7% and 125–250 µm (38.2%) in seagrass bed. Seagrass bed degradation may not only reduce the stock of microplastics in the sediments but also alter their composition. This study initially quantified the contribution of microplastics to organic carbon stocks in seagrass bed sediments and underscored the urgent need for seagrass conservation to mitigate climate change and prevent the remobilization of historically buried microplastics.